2000
DOI: 10.1016/s0014-5793(00)02077-9
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule binding of the Drosophila DMAP‐85 protein is regulated by phosphorylation in vitro

Abstract: The phosphorylation of microtubule-associated proteins (MAPs) is thought to be a key factor in the regulation of microtubule (MT) stability. Previously we isolated DMAP-85, a Drosophila MAP shown to be associated with stable MTs. In this work we show that DMAP-85 phosphorylated in cell-free early embryo extracts is released from MTs. MPM-2 antibodies recognize the phosphorylated protein. In vitro, DMAP-85 can be phosphorylated by the mitotic kinase Polo affecting its binding to MTs and creating MPM-2 epitopes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Recent studies have indicated that the phosphorylation of microtubule-associated proteins plays a critical role in the regulation of microtubule stability (2,5). Several Drosophila pro-…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that the phosphorylation of microtubule-associated proteins plays a critical role in the regulation of microtubule stability (2,5). Several Drosophila pro-…”
Section: Discussionmentioning
confidence: 99%
“…Parental A549 cells were processed and analyzed in the same manner as a control. (2,5). Given that both Asp and DMAP-85 associate also with centrosomes or microtubules and that their interactions are regulated by phosphorylation (2,5) it is tempting to speculate that these human homologues are potential in vivo targets of Plk3.…”
Section: Fig 8 Apoptosis Induced By Plk3-a and Plk3mentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic evidence of the synergy of the polo 1 asp E3 double-mutant phenotype, as well as recent biochemical evidence, supports a role of polo in regulating centrosomal function through asp (23,34,68). Phosphorylation of DMAP-85 by polo was later shown to regulate its in vitro microtubule-binding activity (16). In addition, work with Xenopus egg extracts has suggested that Plx1 can phosphorylate the MAP Op18 and regulate its destabilizing activity (14).…”
mentioning
confidence: 87%
“…These included b-tubulin and two proteins of 85 kDa and approximately 200 kDa. Subsequently, it appears that these last two proteins are likely to be an 85 kDa MT-associated protein released from MTs following phosphorylation by Polo (Cambiazo et al, 2000) and Asp, the product of the abnormal spindle gene (Saunders et al, 1997;Avides and Glover, 1999;Avides et al, 2001;see below).…”
Section: In the Right Place At The Right Timementioning
confidence: 99%